Investigating Retrotransposon Dynamics in Wheat Genotypes Under Salinity Stress: A Comparative Study of In vitro and In vivo Cultivation - Ilman, Gunay Ismayilova; Heybat, Mahira Mammadova; Husni, Tofig Qaragezov; Marakli, Sevgi; Ojaghi, Javid; Mammad, Irada Huseynova (HARD, 2025)
Abiotic stressors have various unexpected effects on plants. Studying the movement activity of retrotransposons in response to these stresses may help to understand their ability to respond to changing environmental conditions. In this study, three local wheat (Gyrmyzy bugda, Jumhuriyet 100, and Nurlu 99) genotypes were taken and the movement activity of retrotransposons under the influence of salinity stress was determined by the IRAP marker method. The movement activity of barley (SUKKULA), rice (HOUBA), and soybean (SIRE1) retrotransposons was studied in wheat genotypes grown under salt stress (150 and 200 mM NaCl) callus culture and leaf samples at 15 and 30 days. At 150 mM NaCl, in 15-day-old callus and leaf samples, 0-83% and 0-50% polymorphism were found, respectively, for the HOUBA retrotransposon. At 200 mM NaCl, the polymorphism in callus and leaf samples amounted to 0-83% and 0-40%, respectively. For SUKKULA retrotransposon, at 150 mM NaCl, in 15-day-old callus and leaf samples, polymorphism was 0-67% and 0-86%, and at 200 mM NaCl, this parameter was found to be 0-67% and 0-89%, respectively. For SIRE1 retrotransposon, at 150 mM NaCl in 15-day-old callus and leaf samples, the polymorphism was 0-75% and 0-88%, while at 200 mM NaCl, it was equal to 0-71% and 0-100%, respectively. This is one of the first studies to examine epigenetic modifications in wheat plants that are developing in Azerbaijan.
Keywords: epigenetics; retrotransposon; IRAP; callus; phylogenetics; TRANSPOSABLE ELEMENTS; LTR-RETROTRANSPOSONS; GROWTH; DNA; Environmental Sciences & Ecology